Pengaruh Subsektor Pertanian Terhadap Produk Domestik Regional Bruto Dalam Perspektif Ekonomi Islam Di Provinsi Lampung - Atika, Ria; Habibi, Ahmad; Ekawati, Evi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The area is quite large and has a large number of workers in the agricultural sector has not been able to maximize the potential of the agricultural sector in Lampung Province. This can be seen from the increase in the growth rate of the agricultural sector which is still very small compared to other sectors. This study aims to examine the influence of the subsectors of food crops, horticulture, plantations, livestock and agricultural services on the gross regional domestic product of Lampung Province in the perspective of Islamic economics. The method used in this study is quantitative. Using secondary data. The population used is the amount of data collected from the productivity data report of the subsectors of food crops, horticulture, plantations, livestock, agricultural services and the rate of GDP from economic sectors on the basis of constant prices according to business fields in Lampung province that have been published by BPS. The research sample used a saturated sample with a total of 56 samples. The results of this study show that the sub-sectors of food crops, horticulture, plantations, livestock, and agricultural services have a positive effect on the gross regional domestic product of Lampung Province. Gross regional domestic product based on the sub-sectors of food crops, horticulture, plantations, and livestock in the perspective of Islamic economics can be seen in the form of justice. Justice taught by Islam aims to prevent wealth from accumulating to certain groups in society.